2015
DOI: 10.17705/1jais.00390
|View full text |Cite
|
Sign up to set email alerts
|

ICT-Enabled Community Empowerment in Crisis Response: Social Media in Thailand Flooding 2011

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 106 publications
4
108
0
1
Order By: Relevance
“…Researchers have demonstrated that SNSs such as Facebook can enhance information sharing (Pan et al, ; Leong, Pan, Ractham, & Kaewkitipong, ; Zagaar & Paul, ; Zhitomirsky‐Geffet & Bratspiess, ), communication and information gathering (Ellison & Boyd, ; Huang, Chu, & Chen, ; Thelwall & Wilkinson, ), and the development of emotional support (Oh & Syn, ). Internet users are increasingly merging their online activities through SNSs (Yu, Tian, Vogel, & Kwok, ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Researchers have demonstrated that SNSs such as Facebook can enhance information sharing (Pan et al, ; Leong, Pan, Ractham, & Kaewkitipong, ; Zagaar & Paul, ; Zhitomirsky‐Geffet & Bratspiess, ), communication and information gathering (Ellison & Boyd, ; Huang, Chu, & Chen, ; Thelwall & Wilkinson, ), and the development of emotional support (Oh & Syn, ). Internet users are increasingly merging their online activities through SNSs (Yu, Tian, Vogel, & Kwok, ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Digital empowerment emphasizes the enabling roles of ICT tools. Extant work suggests structural, resource and psychological empowerment as three key dimensions [22] [23]. Structural empowerment focuses on improving the objective external conditions (such as organizational, institutional, social, economic, political, Page 654 and cultural conditions) to offer the power to take actions [24].…”
Section: A Digital Empowerment Perspectivementioning
confidence: 99%
“…For example, social media has provided a platform to help individuals rise up against social and political injustices [60], such as the Arab Spring in 2011 [53]. Social media has also empowered communities during natural disasters, such as the Thailand Flood [39]. Many individuals use social media to share their experiences, seek out information, connect with others, and find social support [17].…”
Section: Introductionmentioning
confidence: 99%